2010
DOI: 10.1063/1.3352445
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy of cold aluminum cluster anions: Comparison with density functional theory results

Abstract: Photoelectron spectra of cold aluminum cluster anions Al(n)(-) have been measured in the size range n=13-75 and are compared to the results of density functional theory calculations. Good agreement between the measured spectra and the calculated density of states is obtained for most sizes, which gives strong evidence that the correct structures have been found. In particular the results confirm the occurrence of rather different structural motifs in this size range, from fcc-like stacks over fragments of deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 39 publications
11
60
0
Order By: Relevance
“…[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Issendorff and coworkers have also coupled a cryogenic 12-pole linear ion trap with a magnetic-bottle PES analyzer for the study of atomic clusters. 114 The moderate resolution of the magneticbottle analyzer is sufficient for MCAs, for which no slow electrons are possible due to the RCB. However, for singly charged anions, the cryogenic Paul trap offers an opportunity to conduct high-resolution PES using PE imaging.…”
Section: High-resolution Photoelectron Imaging and Spectroscopy Omentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Issendorff and coworkers have also coupled a cryogenic 12-pole linear ion trap with a magnetic-bottle PES analyzer for the study of atomic clusters. 114 The moderate resolution of the magneticbottle analyzer is sufficient for MCAs, for which no slow electrons are possible due to the RCB. However, for singly charged anions, the cryogenic Paul trap offers an opportunity to conduct high-resolution PES using PE imaging.…”
Section: High-resolution Photoelectron Imaging and Spectroscopy Omentioning
confidence: 99%
“…However, we found that for just a few sizes (Al 37,44,66,68 ) with decreasing temperature there appears a bulge-like feature close to the ionization threshold. The clearest and most prominent example is observed in the photoionization spectrum of the closed-shell [9,10,[46][47][48] "magic" cluster Al 66 with 198 valence electrons, as seen in the progression of spectra shown in Fig. 3(b) [43].…”
Section: Temperature-induced Transition In the Spectrummentioning
confidence: 95%
“…Taking, therefore, for an estimate λ b ≈2 together with the Al 66 intershell spacing of δ≈0.3-0.35 eV (deduced from photoelectron spectroscopy data [10,48] as the distance between the half-maximum points on the facing slopes of the topmost peaks), so that ξ in Eq. (2) is ≈0.15-0.17 eV (since μ is located halfway between the highest-occupied and lowest-unoccupied shells [13]), and a characteristic vibrational frequency ~35 meV, it is found that the equation for T c yields a solution of ≈70 K [64].…”
Section: Discussion Of the Transitionmentioning
confidence: 99%
See 2 more Smart Citations